AutoCAD Platform Customization User Interface and Beyond - Ambrosius, Lee (Wiley, 2014)
Make AutoCAD your own with powerful personalization options Options for AutoCAD customization are typically the domain of administrators, but savvy users can perform their own customizations to personalize AutoCAD. Until recently, most users never thought to customize the AutoCAD platform to meet their specific needs, instead leaving it to administrators. If you are an AutoCAD user who wants to ramp up personalization options in your favorite software, AutoCAD Platform Customization: User Interface and Beyond is the perfect resource for you. Author Lee Ambrosius is recognized as a leader in AutoCAD platform customization and can help you get the most out of AutoCAD.Establish and manage CAD standards for the drawings you createControl the startup process and settings that define the drawing environmentModify the user interface to display the commands you use most frequently and create new commandsCreate macros to speed up frequently repeated tasksDefine custom shapes, linetypes, and hatch patters to control the linework in a drawingUse real-world tips and tutorials to reinforce the author's topical discussions A perfect resource for CAD administrators, students, senior drafters, and other CAD enthusiasts, AutoCAD Platform Customization: User Interface and Beyond features in-depth discussions of customization options as well as detailed examples and tutorials. As an eight-year customization and programming session leader with Autodesk University, Lee Ambrosius is uniquely qualified to help users get the most out of software based on the AutoCAD platform. His AutoCAD Platform Customization: User Interface and Beyond is the go-to resource for those who are ready to take their software customization to the next level